RANCANG BANGUN ALAT UJI PERIFERAL ESP32 DEVKIT V1 - DOIT 30 PIN - Adrian Pramuditya, I Made; Raka Agung, I Gusti Agung Pt; Rahardjo, Pratolo (Program Studi Teknik Elektro UNUD, 2023)
The ESP32 DEVKIT V1 - DOIT 30 Pin Peripheral Board Test Tool is a module that can be used to test the ESP32 DEVKIT V1 - DOIT 30 Pin microcontroller board. The chip of the board is ESP32 developed by Espressif Systems. ESP32 has many features or peripherals that can be used in various projects. Built-in Internet of things (IoT) is one of the leading features that can connect the board to the internet without the need for additional modules from outside. Features or peripherals that can be tested on the ESP32 DEVKIT V1 - DOIT 30 Pin Peripheral Board Test Tool, are digital i/o, ADC & DAC, dual core system, built-in touch sensor, built-n hall sensor, Bluetooth, and Wi-Fi.